Polypharmacy and its associated factors among patients with co-morbid hypertension and diabetes in a municipal hospital in Ghana - Adwoa Oforiwaa Kwakye; Irene A. Kretchy; Kwaku Gyamfi Oppong (Scientific African, 2024)
Background/aim: Patients with co-morbid hypertension and diabetes may take several medicines. Although multiple medications may aid in the management of their condition, they also raise the likelihood of drug interactions and unfavorable drug reactions. This study therefore evaluated polypharmacy and its associated factors in patients with co-morbid hypertension and diabetes. Methodology: This was a cross-sectional study with data collection spanning a 3-months period. Patients attending their review clinic in a municipal hospital in Ghana were interviewed with a pre-tested semi-structured questionnaire to collect data on socio-demographic characteristics, prescription medicines, therapeutic lifestyle changes, blood pressure management and fasting blood glucose. Polypharmacy was defined as the use of five or more medicines in a single day. Results: Of the 338 patients with co-morbid hypertension and diabetes, (18 %, n = 61) were men and (82 %, n = 277) were women. Most of the study participants (40.2 %, n = 136) were between 55 and 64 years. Polypharmacy (≥5 medications) was observed in (64.8 %, n = 219) of the participants and being male [cOR = 2.29, 95 % CI (1.18 – 4.42), p = 0.014] and living in a rural setting [cOR = 2.46, 95 % CI (1.13 - 5.34), p = 0.023] were significantly associated with more than the two-fold increased risk of having polypharmacy compared to being female and living in an urban setting respectively. Most patients were on biguanides (89.1 %, n = 301), angiotensin receptor blockers (68.6 %, n = 232), calcium channel blockers (66.6 %, n = 225) and sulphonylurease (53.8 %, n = 182). Conclusion: Polypharmacy is common in patients with co-morbid hypertension and diabetes, and is associated with sex, marital status, and residential status. Healthcare providers must carefully consider these associated factors when prescribing or modifying treatment plans for their patients.